Dependable-cooperative channel resource allocation scheme in wireless mesh network - Mingming LI; Guangxue YUE; Shaoqing DAI; Bolin MA (Dianxin kexue)
For improving utilization of channel resources and service quality effectively in wireless mesh network,a dependable-cooperative channel resource allocation scheme was proposed.According to the adaptive features of mesh node,engaging game theory and establishing reputation mechanism to achieve dependable-cooperative of nodes,and channel resource allocation result was utilized.The comparison of this experiment proves the situation of service level and network utility of cooperative service.The result of it shows that networks benefit will be optimal when the cooperative service level is 3 and node hops synergies with the service level.Comparing with classic syn-ergetic algorithm,with the same context of network topology,dependable-cooperative channel allocation strategy is clearly dominated with 1.04 on UACRR and 1.069.